Exploiting the Repetitive Fraction of the Wheat Genome for High‐Throughput Single‐Nucleotide Polymorphism Discovery and Genotyping. Issue 1 (1st March 2016) - Cubizolles, Nelly; Rey, Elodie; Choulet, Frédéric; Rimbert, Hélène; Laugier, Christel; Balfourier, François; Bordes, Jacques; Poncet, Charles; Jack, Peter; James, Chris; Gielen, Jan; Argillier, Odile; et al.
Abstract : Transposable elements (TEs) account for more than 80% of the wheat genome. Although they represent a major obstacle for genomic studies, TEs are also a source of polymorphism and consequently of molecular markers such as insertion site‐based polymorphism (ISBP) markers. Insertion site‐based polymorphisms have been found to be a great source of genome‐specific single‐nucleotide polymorphism (SNPs) in the hexaploid wheat ( Triticum aestivum L.) genome. Here, we report on the development of a high‐throughput SNP discovery approach based on sequence capture of ISBP markers. By applying this approach to the reference sequence of chromosome 3B from hexaploid wheat, we designed 39, 077 SNPs that are evenly distributed along the chromosome. We demonstrate that these SNPs can be efficiently scored with the KASPar (Kompetitive allele‐specific polymerase chain reaction) genotyping technology. Finally, through genetic diversity and genome‐wide association studies, we also demonstrate that ISBP‐derived SNPs can be used in marker‐assisted breeding programs.